Impact of social distancing related to COVID-19 in patients with temporomandibular disorder - Delazere Teles, Gabrielle; Colares da Costa Otavio, Andressa; de Lavra Pinto Aleixo, Bárbara; Dantur Batista Chaves, Karen (Revista da Faculdade de Odontologia de Porto Alegre, 2023)
Aim: To evaluate the impact of the social distancing imposed by COVID-19 in the socioeconomic, familiar and health scope of the participants, as well as the relation of the gravity of the sign and symptoms of Temporomandibular disorder. Materials and methods: Two questionnaires were applied, one by telephone interview and the other virtual. The first asked about signs and symptoms of temporomandibular disorder and the second about behavior during the pandemic. Results: The sample was composed by 15 patients, mostly women who lived in Porto Alegre. 64,3% of the subjects declared there was a decrease in household income during this period. Concerning to difficulties found to access health service, make an appointment, and get health care, were the most cited, each pointed to 61,5% of the sample. The presence of anxiety and depression feelings were cited 64,3%. There was an increase in alcohol consumption during the pandemic as a decrease in the frequency of physical activity. Discussion: Several studies that were conducted during and after the pandemic, corroborate the findings that the social distancing cause negative repercussions in the mental health, socioeconomics situations and in the daily habits in the population from all over the world. Conclusion: With this study we could observed and analyzed how the patients who suffered with TMD faced the challenges proposed by the social distancing, due to COVID-19. We can conclude that the pandemic causes several negatives effects in most of the group.